CURRENT SITUATION OF HUMAN RESOURCE TRAINING MANAGEMENT AT HO CHI MINH CITY DENTAL AND MAXILLOFACIAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Health human resources play a pivotal role in ensuring the quality of healthcare services, in which training management is a key factor for enhancing professional capacity and patient safety.Objective: To describe the current status of human resource training management at Ho Chi Minh City Odonto-Stomatology Hospital in 2023.Materials and Methods: A descriptive cross-sectional study was conducted using secondary data from personnel and training management reports provided by the Department of Organization and Personnel of Ho Chi Minh City Odonto-Stomatology Hospital in 2023.Results: The proportion of permanent staff increased from 61,1% to 78,7% in 2023, while the proportion of non-permanent contract workers decreased from 38,9% to 21,3%. The workforce was predominantly female (57,8% in 2022 and 58,3% in 2023), with the majority aged 30–50 years (over 70,5%). Staff holding university degrees accounted for 49%, while those with postgraduate qualifications accounted for 26,5%. Training activities mainly focused on short-term training programs (64,4%), whereas postgraduate training such as Specialist Level I (11,9%), Specialist Level II (9,9%), Master’s and Doctoral programs (each 5,9%) accounted for lower proportions.Conclusion: The management of human resource training at the hospital indicates a current priority on meeting immediate professional demands through short-term training programs. However, it is necessary to develop a long-term training strategy to increase the proportion of staff with postgraduate qualifications, thereby contributing to the sustainable development of a high-quality healthcare workforce.
Keywords: Training management; health human resources; continuing education; odonto-stomatology hospital.